Description of previously unknown females of three Euriphene Boisduval, 1847 species and the unknown male of Bebearia inepta Hecq, 2001 from Western Africa, with notes on their taxonomy, bionomy and distribution (Lepidoptera: Nymphalidae, Limenitidinae) - Sz. Sáfián; S. C. Collins; C. Belcastro; O. Brattström; R. Tropek (SHILAP)
During extensive field research of fruit-feeding Lepidoptera in various West African forests, we have collected a rich material of several rare or poorly known species. Among them we identified four species, where only one of the sexes was described. Here, we describe unknown females of Euriphene lomaensis Belcastro, 1986, E. taigola Sáfián & Warren-Gash, 2009 and E. bernaudi Hecq, 1994 with reference to the latter species’ taxonomic position (stat. rev.). We also describe the male of Bebearia inepta Hecq, 2001. We report observations on their habitats and behaviour and review their known distribution.